Peran Majelis Dikdasmen Pimpinan Cabang Muhammadiyah Kartasura dalam Meningkatkan Mutu Pendidikan Sekolah Muhammadiyah di Kecamatan Kartasura Tahun 2012-2015 - Istabroqin, Istabroqin; , Dr. M. Abdul Fattah Santoso, M.Ag (2016)
In 1911 (nineteen eleven), precisely on 1 st December, KH. Ahmad Dahlan established an institution named "Madrasah Ibtidaiyah Islamiyah" (The Islamic Primary School) as a pioneer to establish an assemly of primary and secondary education (Dikdasmen) of which up to now expanding for establishing and develoving schools of Muhammadiyah's education to be better. Generally, the assignment and assembly function from the center level till upper level as like as the organizer charity efforts, programs, primary and secondary education's activites like trust policy. The assembly of primary and secondary education have to organize, guide, advise and control in very school of Muhammadiyah included that to increase education grade there, so that the assembly of primary and secondary (Dikdasmen) have to get working relation with headmasters. The research purposed to know: 1) the efforts are done by assembly of primary and secondary education of Muhammadiyah Surakarta in increasing education grade of Muhammadiyah schools in the subdistrict of Kartasura; 2) supporting and obstacle faktors of assembly of primary and secondary education of Muhammadiyah Kartasura management for increasing education grade of Muhammadiyah schools in subdistrict of Kartasura. This reseach is kind of square research, and the method used interview and documentation method as data source. So that, the descriptive qualitive of analysis is writer's mothod to analize the data. From this research, we took the conclusions, including: 1) The assembly of primary and secondary education (Dikdasmen) of Muhammadiyah management of Surakarta runs working program that refer to eighat standards of education grade. Working program which is suitable with standard of education grade is covering standard content: to do upgrading of subjects nor curriculum which UMS (Muhammadiyah University of Surakarta). Processing standard: to do comparative study to the other Muhammadiyah schools which have good education grade; to do visiting of working to schools once in semester. Management standards: to do conduct training towards teachers and employees once in a month. Financial standard: to do upgrading especially in financial management. 2) of the supporting factors that between integrated Islamic of primary school (SDIT) and Muhammadiyah Islamic school are nothing in common. But between sample school and assembly of primary school, there are similarities such as: the director general of education helps them by giving local class, to do cooperation with Muhammadiyah University of Surakarta (UMS). Whereas the obstacle factor is we know that berween integrated islamic of primary school and Muhammadiyah Islamic school have an obstacle similarity and that is financial problem.